2016
DOI: 10.3390/antibiotics5010011
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Modalities and Antimicrobial Stewardship Initiatives in the Management of Intra-Abdominal Infections

Abstract: Antimicrobial stewardship programs (ASPs) focus on improving the utilization of broad spectrum antibiotics to decrease the incidence of multidrug-resistant Gram positive and Gram negative pathogens. Hospital admission for both medical and surgical intra-abdominal infections (IAIs) commonly results in the empiric use of broad spectrum antibiotics such as fluoroquinolones, beta-lactam beta-lactamase inhibitors, and carbapenems that can select for resistant organisms. This review will discuss the management of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
(133 reference statements)
0
11
0
Order By: Relevance
“…A growing body of evidence demonstrates that hospital based programs dedicated to improving antibiotic useASPs-can both optimize the management of infections and reduce adverse events associated with antibiotic use [19][20][21][22]. Ten years after the jointly published guidelines by the Centers for Disease Control and Prevention, Society for Healthcare Epidemiology of America, and Infectious Diseases Society of America, however, many acute care centers worldwide do not have any type of antimicrobial improvement program [23].…”
Section: Antimicrobial Stewardship Programs (Asps) In Surgical Departmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence demonstrates that hospital based programs dedicated to improving antibiotic useASPs-can both optimize the management of infections and reduce adverse events associated with antibiotic use [19][20][21][22]. Ten years after the jointly published guidelines by the Centers for Disease Control and Prevention, Society for Healthcare Epidemiology of America, and Infectious Diseases Society of America, however, many acute care centers worldwide do not have any type of antimicrobial improvement program [23].…”
Section: Antimicrobial Stewardship Programs (Asps) In Surgical Departmentioning
confidence: 99%
“…Hoffmann et al [20] published a review focusing on treatment modalities and antimicrobial stewardship initiatives in the management of IAIs. The authors concluded that to prevent the overuse of broad-spectrum agents, ASPs should work with their microbiology department.…”
Section: Call To Action For Surgeons 627mentioning
confidence: 99%
“…Clostridium difficile and organ damage. 6,8,10,14,51 The use of antibiotics impacts not only the individual recipient, but also others that may be colonized or infected by resistant bacteria. 50,52 The gain of constitutionally resistant pathogens and selective pressure for resistance in the unit, hospital or community is of rising consideration.…”
Section: Consequences Of Antibiotics Misusementioning
confidence: 99%
“…56 Due to the limited development of new antibiotics, particularly for gram-negative microorganisms, the careful use of antibiotic therapy is essential to hold the resistance rates and preserve the existent antibiotics. 10,52,55,57 Antimicrobial stewardship programs (ASP) can promote a better use of antibiotic therapy, de-escalation and reduce unsuitable prolonged durations of treatment, 8,18 being vital to hold and control resistance. 10,52,57 They are also important to promote public understanding of the danger of antimicrobial resistance.…”
Section: Consequences Of Antibiotics Misusementioning
confidence: 99%
See 1 more Smart Citation